2013
DOI: 10.1039/c3nr02129g
|View full text |Cite
|
Sign up to set email alerts
|

Specific biomolecule corona is associated with ring-shaped organization of silver nanoparticles in cells

Abstract: We correlate the localization of silver nanoparticles inside cells with respect to the cellular architecture with the molecular information in the vicinity of the particle surface by combining nanoscale 3D cryo-soft X-ray tomography (cryo-SXT) with surface-enhanced Raman scattering (SERS). The interaction of the silver nanoparticle surface with small molecules and biopolymers was monitored by SERS in vitro over time in living cells. The spectra indicate a stable, time-independent surface composition of silver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(90 citation statements)
references
References 52 publications
9
80
0
1
Order By: Relevance
“…Within the cell, the Ag-NPs formed aggregates in the cytoplasm and did not reach mitochondria or the nucleus. The formation of nanoparticle clusters within the cytoplasma of cells was already reported by different groups [3,24,25] and various studies have suggested an endocytotic uptake mechanism for Ag-NP [3,26]. Whether the Ag-NPs reach the nucleus often depends on the NP size, as the diameter of the nuclear pores is about 20-50 nm depending on the cell type [27,28].…”
Section: Inflammatory Reaction In Pbcecmentioning
confidence: 92%
“…Within the cell, the Ag-NPs formed aggregates in the cytoplasm and did not reach mitochondria or the nucleus. The formation of nanoparticle clusters within the cytoplasma of cells was already reported by different groups [3,24,25] and various studies have suggested an endocytotic uptake mechanism for Ag-NP [3,26]. Whether the Ag-NPs reach the nucleus often depends on the NP size, as the diameter of the nuclear pores is about 20-50 nm depending on the cell type [27,28].…”
Section: Inflammatory Reaction In Pbcecmentioning
confidence: 92%
“…Such junctions give rise to local field "hotspots" which are the source of the SERS effect in many studies, and are typically excited by source wavelengths of >600nm. For example, Drescher et al have demonstrated that the acidic environment of endosomes causes nanoparticle aggregation into dimers and trimers leading to an increased SERS effect at 785 nm 16 . Bonifacio et al have demonstrated that negligible SERS effects are observable in human serum samples, in which the serum proteins form a protein corona 33,34 , which coats the nanoparticles and prevents them from aggregating and forming hotspots, whereas, once the proteins are filtered out, strong and reproducible SERS signals can be recorded, again using 785 nm as source 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after the addition was complete, the mixture was brought to the boil and maintained at this temperature for ~30 min. In order to evaluate the effect of aggregation on SERS from the gold nanospheres, acidic conditions were employed to induce nanoparticle aggregation 16 . HCl at a concentration of 1 M was added dropwise to aqueous suspensions of 150 nm nanospheres and the pH value was adjusted between 7 to 4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were incubated with such a mixture for 3 h. When both SEHRS labels were applied, the cells were incubated with 2-NAT SEHRS labels in culture medium for 3 h, and after washing with PBS, they were incubated with pMBA SEHRS labels in the culture medium, also for 3 h. After incubation, the cells were washed thoroughly with PBS buffer, in which they were also kept during the measurements. We have investigated the cytotoxicity of silver nanoparticles 33 and of the reporter molecules 11 in similar experiments, and found that no toxicity was associated under these experimental conditions with either of them, specifically with the concentrations used here.…”
Section: Application Of Sehrs Labels In Cellsmentioning
confidence: 99%